2014
DOI: 10.1097/inf.0000000000000104
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Intrafamilial Oropharyngeal Transmission of Kingella Kingae

Abstract: Abstract:To evaluate the intrafamilial oropharyngeal transmission of Kingella kingae, we conducted a prospective study among pairs of siblings. We found that 55% of children who suffered from osteoarticular infections due to K. kingae, and 40% of asymptomatic carriers of K. kingae had siblings with positive oropharyngeal carriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The research found that 55.0% of children with a PCR-documented invasive K. kingae infection and 40.0% of asymptomatic carriers had siblings with a positive pharyngeal PCR assay, suggesting dissemination of the organism within susceptible family members (108).…”
Section: Transmissionmentioning
confidence: 99%
“…The research found that 55.0% of children with a PCR-documented invasive K. kingae infection and 40.0% of asymptomatic carriers had siblings with a positive pharyngeal PCR assay, suggesting dissemination of the organism within susceptible family members (108).…”
Section: Transmissionmentioning
confidence: 99%
“…Kingella kingae colonises the oropharynx and spreads through droplets of buccal secretions among young siblings and playmates 4,21,22 . Crowded conditions, such as those prevalent in day care centres, facilitate child‐to‐child transmission 4,23 .…”
Section: Resultsmentioning
confidence: 99%
“…Kingella kingae colonises the oropharynx and spreads through droplets of buccal secretions among young siblings and playmates. 4,21,22 Crowded conditions, such as those prevalent in day care centres, facilitate child-to-child transmission. 4,23 Colonisation commences after the age of 6 months, suggesting that maternally derived immunity, coupled with limited socialisation, prevents early acquisition of the bacterium.…”
Section: Carriage and Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organism is carried in the oropharynx without clinical symptoms and is transmitted from child to child by close contact among siblings and playmates (4)(5)(6)(7). The colonized mucosal surface is also the portal of entry of K. kingae to the bloodstream, from where it may invade the skeletal system and the endocardium, for which the species exhibits a particular tropism (8-10).…”
mentioning
confidence: 99%